2018
DOI: 10.1093/nar/gky863
|View full text |Cite
|
Sign up to set email alerts
|

A monovalent ion in the DNA binding interface of the eukaryotic junction-resolving enzyme GEN1

Abstract: GEN1 is a member of the FEN/EXO family of structure-selective nucleases that cleave 1 nt 3′ to a variety of branchpoints. For each, the H2TH motif binds a monovalent ion and plays an important role in binding one helical arm of the substrates. We investigate here the importance of this metal ion on substrate specificity and GEN1 structure. In the presence of K+ ions the substrate specificity is wider than in Na+, yet four-way junctions remain the preferred substrate. In a combination of K+ and Mg2+ second stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
(60 reference statements)
0
6
0
Order By: Relevance
“…This mechanism is proposed to ensure that the second cleavage takes place within the lifetime of the resolvase-HJ complex. The acceleration of the second cleavage was reported in quantitative kinetic studies based on the supercoiled cruciform substrate which showed 11-fold (61) and 17-fold acceleration of the second strand cleavage of the junction in presence of Mg 2+ and K + ions (55). We cannot assign the rates of the first and the second incisions nevertheless we can measure the dimer lifetime on the nicked and intact HJs.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…This mechanism is proposed to ensure that the second cleavage takes place within the lifetime of the resolvase-HJ complex. The acceleration of the second cleavage was reported in quantitative kinetic studies based on the supercoiled cruciform substrate which showed 11-fold (61) and 17-fold acceleration of the second strand cleavage of the junction in presence of Mg 2+ and K + ions (55). We cannot assign the rates of the first and the second incisions nevertheless we can measure the dimer lifetime on the nicked and intact HJs.…”
Section: Discussionmentioning
confidence: 91%
“…Nonetheless, the prominent similarity between k STO and k Max-app indicates that the majority of the reaction time in smFRET is used for catalysis by GEN1 dimer. The cleavage activity of Ct GEN1 varied with different monovalent ions showing 2-fold increase in K + compared to Na + in the presence of Mg 2+ (55). Performing the cleavage reaction using human GEN1 1–527 in Tris buffer pH 7.5 and either K + or Na + at the standard 22°C, the rates were comparable but just slightly higher in Na + than in K + (Supplementary Figure S5D).…”
Section: Resultsmentioning
confidence: 99%
“…Within junctions are processed by the cytoplasmic GEN1 (Yen1 in budding yeast) nuclease that acts during late M-phase and anaphase (14)(15)(16). GEN1 function as a homodimer, resolving junctions by two sequential cleavage reactions (17)(18)(19). The properties of GEN1 are very similar to junctionresolving enzymes of lower organisms and phage (20).…”
Section: Introductionmentioning
confidence: 99%
“…However, eukaryotic Rad2/XPG family HJ resolvases are monomeric in solution and dimerization happens on the HJ ( 40 , 47 , 48 , 53 ). It has been shown for human GEN1 that dimerization on the HJ substrate stimulates the first incision of the junction by one of the monomers, which is the rate-limiting step for HJ resolution ( 40 ), while experiments with CtGEN1 have confirmed that cleavage of the second strand is accelerated after the first incision ( 48 , 100 ). To test if the formation of the dimer on a HJ could also favour the initial incision by Yen1, we created a modified X0 HJ with a SP bond at the expected cleavage position of Yen1 in oligo X0-3, between nucleotides 31 and 32 (Figure 7A ).…”
Section: Resultsmentioning
confidence: 99%